2010
DOI: 10.1007/s11604-010-0449-6
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of positron emission tomography/computed tomography and plasma osteopontin levels in patients with asbestos-related pleural disease

Abstract: PET/CT might be more helpful than plasma osteopontin for distinguishing benign asbestos-related pleural diseases from MPM, and the SUVmax in benign asbestos-related pleural diseases may reflect changes in pleural inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…PET is based on the differential metabolism of normal and abnormal tissues, and the uptake of 18 F-FDG is usually accelerated in tumor cells. Because some pleural inflammatory and infectious lesions can also induce increased 18 F-FDG uptake, the underlying diseases may display false-positive findings, leading to a low diagnostic accuracy for PET-CT. To improve diagnostic ability, various methods of interpreting PET-CT, including the use of SUV threshold, ratio of SUV of pleural lesions to that of mediastinum, and dual-time-point PET have been proposed [ 9 , 10 , 17 , 18 ]. However, the concern about false-negative results still remains.…”
Section: Discussionmentioning
confidence: 99%
“…PET is based on the differential metabolism of normal and abnormal tissues, and the uptake of 18 F-FDG is usually accelerated in tumor cells. Because some pleural inflammatory and infectious lesions can also induce increased 18 F-FDG uptake, the underlying diseases may display false-positive findings, leading to a low diagnostic accuracy for PET-CT. To improve diagnostic ability, various methods of interpreting PET-CT, including the use of SUV threshold, ratio of SUV of pleural lesions to that of mediastinum, and dual-time-point PET have been proposed [ 9 , 10 , 17 , 18 ]. However, the concern about false-negative results still remains.…”
Section: Discussionmentioning
confidence: 99%
“…Kurata et al have investigated the role of PET and osteopontin levels in asbestos related pleural disease and concluded that malignant mesothelioma has significantly higher uptake than benign asbestos related pleural disease (1). There is limited number of studies in the literature about asbestos related pleural disease in the literature (3).…”
Section: Discussionmentioning
confidence: 99%
“…There is limited number of studies in the literature about asbestos related pleural disease in the literature (3). Kurata et al accepted a SUV max level of 4.1 and orki et al as 3.0 for determination of malignancy (1,3). However the authors stressed about the epitheloid subtype of malignant mesothelioma which is a slow growing variant of the group that has SUV max levels around 2.0 (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of positron emission tomography (PET) and integrated PETcomputer tomography (PET-CT) with [18] F-Fluorodeoxyglucose (FDG) in predicting malignancy in patients with pleural effusion or pleural thickening is still debated. The existing three earlier systematic reviews and meta-analyses were published in 2014 and 2015, included also noneffusion pleural pathology [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], handled bias differently, and reached different and contradictory conclusions [23][24][25]. Five studies have been published since then [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%